2018
DOI: 10.1038/s41538-017-0009-x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of triacylglycerol oxidation mechanisms in canola oil using liquid chromatography–tandem mass spectrometry

Abstract: Triacylglycerol (TG), the main component of edible oil, is oxidized by thermal-or photo-oxidation to form TG hydroperoxide (TGOOH) as the primary oxidation product. Since TGOOH and its subsequent oxidation products cause not only the deterioration of oil quality but also various toxicities, preventing the oxidation of edible oils is essential. Therefore understanding oxidation mechanisms that cause the formation of TGOOH is necessary. Since isomeric information of lipid hydroperoxide provides insights about oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(111 citation statements)
references
References 47 publications
(61 reference statements)
6
103
1
Order By: Relevance
“…To the best of our knowledge, this is the first study that quantitatively analyzed the amounts of SQOOH isomers contained in food samples. Total amounts of SQOOH isomers accounted for >0.1% of the contents of SLO supplements (1.26–5.70 mg/g), which represent a high amount compared with previously reported values of lipid hydroperoxides in food products (e.g., about 10 µM in edible oils) . The high content of SQOOH may be attributed to the high susceptibility of squalene to oxidation, and thus illustrates the value in evaluating ways to prevent squalene oxidation in foods.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study that quantitatively analyzed the amounts of SQOOH isomers contained in food samples. Total amounts of SQOOH isomers accounted for >0.1% of the contents of SLO supplements (1.26–5.70 mg/g), which represent a high amount compared with previously reported values of lipid hydroperoxides in food products (e.g., about 10 µM in edible oils) . The high content of SQOOH may be attributed to the high susceptibility of squalene to oxidation, and thus illustrates the value in evaluating ways to prevent squalene oxidation in foods.…”
Section: Resultsmentioning
confidence: 51%
“…We previously reported the analysis of SQOOH isomers in human SSLs by using LC−MS/MS with atmospheric pressure chemical ionization (APCI), but due to the nature of APCI fragmentation, fragment ions with similar patterns were produced, making it difficult to selectively analyze SQOOH isomers . Thus, we recently developed an improved method that can selectively and sensitively analyze SQOOH isomers on the basis of evidence that the analysis of sodium adducts during LC−MS/MS analysis enables the selective analysis of other lipid hydroperoxide isomers . With the use of this method, we investigated the oxidation mechanisms of squalene and identified that singlet oxygen oxidation of squalene forms six SQOOH isomers in nearly equal amounts, whereas free radical oxidation mainly forms 2‐ and 3‐OOH‐SQ .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, first, concentrations of nine fatty acids 1 -9 i.e., Acid-i i 1 -9 contained in vegetable oils 1 -8 were determined, via gas chromatography GC 34,35 . Second, measurements of the rate constants k Q LH S and k Q LH t 1/2 were performed for five fatty acid esters LH I -V Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The acid value is a measure of free fatty acids (FFA), but it also provides an indirect measure of the free glycerin obtained due to the hydrolysis of the oil (Vitz et al 2019). An increment in FFA for IMME compared with Indian mango seed oil, as seen in Table 3, suggests hydrolysis of the triglycerides present in the oil (Kato et al 2018). Oils having higher acid value contain more free glycerin and can cause functional problems such as fuel filter clogging and may later lead to reduction in the life of the mud circulation equipment (Arogba and Omede 2012).…”
Section: Chemical Propertiesmentioning
confidence: 99%